Effect of abc Pressing at 573 K on the Microstructure and Martensite Transformation Temperatures in Ti49.8Ni50.2 (at%) - Oleg Kashin; Aleksandr Ivanovich Lotkov; Victor Grishkov; Konstantin Krukovskii; Dorzhima Zhapova; Yuri Mironov; Natalia Girsova; Olga Kashina; Elena Barmina (Metals, 2021)
This paper presents experimental data on the microstructure and martensite transformation temperatures of Ti49.8Ni50.2 (at%) after abc pressing (multi-axial forging) to different true strains e from 1.84 to 9.55 at 573 K. The data show that increasing the true strain results in grain–subgrain refinement on different scales at a time. With e = 9.55 at 573 K, the average grain–subgrain size measured approximately 130 nm. Decreasing the abc pressing temperature from 723 to 573 K caused a decrease in all martensite transformation temperatures, a change in the lattice parameters, R phase formation, and angular shifts of diffraction peaks and their broadening. The largest change in the microstructure of Ti49.8Ni50.2 was provided by abc pressing to e = 1.84. Increasing the true strain to e = 9.55 resulted in a much smaller effect, suggesting that the alloy obtained a high density of structural defects even at e = 1.84. Two possible mechanisms of grain–subgrain refinement are discussed.